Drop size correlation and population balance model for an agitated‐pulsed solvent extraction column. Issue 8 (19th June 2020) - Tan, Boren; Lan, Minle; Li, Longxiang; Wang, Yong; Qi, Tao
Abstract: Agitated‐pulsed column (APC) is a newly designed extraction column with excellent mass transfer performance. In this work, Sauter mean drop diameter d 32 and drop size distribution was investigated under different operation conditions in a 25 mm diameter APC. The results show that with an increase in pulsation intensity and agitation speed the drop size distribution is narrowed and d 32 is decreased significantly. With increasing dispersed‐phase velocity, d 32 increased and drop size distribution become narrow, while there was no noticeable change with continuous velocity. The cumulative size distribution was found to be predicted well using the Inverse Gaussian function. A new correlation was proposed to predict the experimental d 32 data of the APC column used in this study. Furthermore, population balance model was applied to predict the drop size distribution with refitted parameters in the breakage, coalescence kernels functions.